1 - Guerre et formation de l’Etat au Sahel - Saidou, Abdoul Karim (Africa Development, 2024)
This article analyses State formation in the Sahel based on the “warmongering” model developed by Charles Tilly. It aims at showing how the war on terrorism affects the dynamics of State formation in the region. From the Burkina Faso case study, the results show how war creates a double dynamic. First, insecurity-combating policies contribute to extending the coercive apparatus of the State and relaunching the national construction project. Security cooperation and self-defense management groups, then, induce a dynamic of State disintegration marked by its downgrading and hybridisation. While strengthening the State on a military and political level, the war accentuates its patronisation, its marginalisation, and its informalisation. If war accelerates State formation, it is a separate State, which, in some respects, departs from the ideal-typical Weberian model.